Dirac spinor’s transformation under Lorentz mappings - Montiel-Pérez, J Yaljá; López-Bonilla, J; del Moral, M Salazar (Annals of Mathematics and Physics, 2021)
For a given Lorentz matrix, we deduce the Dirac spinor’s transformation in terms of four complex quantities.